Utilizing Demonstrations in Teaching, with an Example Demonstration of Propagation via Cuttings: AEC643/WC306, 5/2018 - Damiani, Isabella; Thoron, Andrew C.; Bunch, James C. (EDIS, 2018)
In a learning environment, it is important to provide instruction to each type of learner. This 4-page document discusses utilizing demonstrations for different types of learners and includes a sample demonstration of plant propagation. Written by Isabella Damiani, Andrew Thoron, and J. C. Bunch and published by the UF/IFAS Department of Agricultural Education and Communication, May 2018. Revised January 2021. http://edis.ifas.ufl.edu/wc306 NOTE: This publication was revised in 2021 to remove verbatim text used from an uncited source.